PENERAPAN PAJAK PROGRESIF TERHADAP PEMILIK KENDARAAN BERMOTOR DITINJAU BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2009 TENTANG KETENTUAN TARIF PAJAK PROGRESIF - Nurul Akbar (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
ABSTRACT             The tax is applied progressively on the ownership of private vehicles both two or more wheels or four or more wheels with the same name of the owner and/or residential address. Progressive taxes are imposed to provide the principle of fairness in tax imposition. Indirectly, the acquisition of this tax is used to improve transportation facilities and develop public transportation. In addition, this progressive policy is also aimed at curbing the growth rate of motor vehicle consumption. In carrying out regional autonomy, local governments have the right, authority, and obligation to take care of their own government or society specifically in implementing the Decentralization policy. The basis of the implementation of motor vehicle taxation is Law No. 28/2009 concerning regional taxes and regional user fees. To increase PAD (Regional Original Revenue), local governments must maximize their progressive tax collection policies for motor vehicle ownership.            So it can be concluded 1). The application and implementation of Progressive Tax in Bandung are guided by Regional Regulation No. 13 of 2011 concerning Regional Taxes, effective on January 1, 2012, which also regulates the taxation of vehicle ownership by taxpayers of more than 1 (one) unit. Implementation of progressive fee collection on 4 (four) wheeled and 2 (two) wheeled motorized vehicles applies the calculation, namely: to ownership. First 1.75%, Second 2.25%, Third 3.75%, Fourth 3.25%, Fifth 3.75% Ownership of motor vehicles for the determination of progressive motor vehicle tax based on the same name and/or address. 2). Factors affecting the implementation of progressive taxes on motor vehicle owners are reviewed based on Act Number 28 of 2009 concerning Progressive Tax Rates: a). Service Quality, b). Tax Paying Awareness, c). Knowledge of Taxation Regulations, d). Understanding of Taxation Regulations e). Perception of the Effectiveness of the Taxation System f). Quality of Service Against Taxpayers, g). Willingness to pay taxes.Keywords: Progressive Tax, Tax Rates, Motorized Vehicles